2009
DOI: 10.1111/j.1600-079x.2009.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves placental efficiency and birth weight and increases the placental expression of antioxidant enzymes in undernourished pregnancy

Abstract: Melatonin participates in circadian, seasonal and reproductive physiology. Melatonin also acts as a potent endogenous antioxidant by scavenging free radicals and upregulating antioxidant pathways. The placenta expresses melatonin receptors and melatonin protects against oxidative damage induced in rat placenta by ischemia-reperfusion. One of the most common complications in pregnancy is a reduction in fetal nutrient delivery, which is known to promote oxidative stress. However, whether melatonin protects place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 63 publications
6
122
1
4
Order By: Relevance
“…Furthermore, there is evidence that melatonin might be a key hormone in fetal life, improving utero-placental hemodynamics and reducing placental oxidative stress in pregnancies complicated with IUGR [59,60] and in animal models of maternal undernutrition [61,62]. The lower melatonin levels in male MUN offspring was not paralleled by a reduction in TAC values and therefore, its contribution in the pool of direct scavengers might not be relevant in this model.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, there is evidence that melatonin might be a key hormone in fetal life, improving utero-placental hemodynamics and reducing placental oxidative stress in pregnancies complicated with IUGR [59,60] and in animal models of maternal undernutrition [61,62]. The lower melatonin levels in male MUN offspring was not paralleled by a reduction in TAC values and therefore, its contribution in the pool of direct scavengers might not be relevant in this model.…”
Section: Discussionmentioning
confidence: 90%
“…All scans ended before the dark phase (19:00). Ultrasound evaluations took place on days 48 (baseline measurements), 50,60,70,80,90,100, and 110 of gestation. Color Doppler ultrasound scans were performed at a constant flow gain setting of 10 and flow filter setting of 2.…”
Section: Methodsmentioning
confidence: 99%
“…Therapeutic supplements thought to target placental blood flow and nutrient delivery to the fetus have been shown to increase fetal growth in animal models of intrauterine growth restriction (IUGR) (50,52,64); however, few studies have addressed uteroplacental hemodynamics in models of improved fetal growth. Moreover, fetal organ development and functional capacity may be altered by supplementing the dam with melatonin throughout gestation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that melatonin reduces oxidative stress and cell damage in the immature fetal sheep brain in response to severe hypoxia [20], and, in fetal and neonatal rats, melatonin improves indices of brain mitochondrial injury and protects against hippocampal cell loss following cerebral ischemia and reperfusion [24,25,26]. Melatonin also demonstrates anti-inflammatory properties, stimulates placental expression of antioxidant enzymes, increases placental efficiency and enhances umbilical flow in compromised pregnancies [27,28,29]; all actions which are likely to protect the developing fetus.…”
Section: Introductionmentioning
confidence: 99%